HUBUNGAN KONSUMSI MIE INSTAN DENGAN STATUS GIZI PADA BALITA USIA 24 – 59 BULAN DI DESA JAMUS KECAMATAN MRANGGEN KABUPATEN DEMAK, INDONESIA TAHUN 2015 - Bulan Putri Intan Raisa Cindy; Suyatno Suyatno; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Developments in information technology and the industry provides direct and indirect effects in the form of a change in lifestyle, which like fast food. Fast food like instan noodlefor food most beloved by all kinds of people. One pack of instan noodles containing high protein and carbohydrates, but low in energy, fat, fiber, and vitamins. Instan noodle consumption is often given to the toddler. Toddlers who eat instant noodles too often will affect the nutritional status. This study aims to determine the relationship of instant noodles consumption with nutritional status of infants 24-59 months in the village Jamus Subdistict Mranggen Regency of Demak in 2015. This type of research is explanatory research and cross sectional approach. The population is all children aged 24-59 months in the village Jamus totaling 50 people. Number of samples 44 people by using purposive sampling that the sample is selected according to criteria of research so as to represent the characteristics of the population. Data were collected by questionnaires, then tested for normality using the Test Kolmogorov Smirrnov significance of less than 0.05 results obtained distribution data is not normal. Researchers used a statistical test of Rank Spearman Test (r) because the data is not on normal distribution with the meaning rate was 95% (ρ <0.05). The results showed have correlation of the energy sufficiency with nutrition status (p = 0.000), and there is have correlation sufficiency of protein with nutritional status (p = 0.045). Not have correlation on % contribution energy and protein of instant noodle with nutrition status. This study recommends that more health workers to increase education about the need to adopt a balanced message by providing nutritious foods, as well as for the public to pay more attention to daily food consumption day by providing extra food just right so adequate intake is balanced and has a normal nutritional status.